Impact of Therapeutic Plasma Exchange on Hemodynamic Parameters in Medical Intensive Care Unit Patients: An Observational Study. Issue 2 (28th April 2016) - Lahmer, Tobias; Messer, Marlena; Schnappauf, Christopher; Rasch, Sebastian; Fekecs, Lisa; Beitz, Analena; Eser, Stefan; Schmid, Roland M.; Huber, Wolfgang
Abstract: Therapeutic plasma exchange (TPE) is an extracorporeal treatment with reported beneficial as well as detrimental effects on circulation. However, there is a lack of data using advanced hemodynamic monitoring during TPE. Therefore, we investigated the effects of TPE on hemodynamic parameters derived from transpulmonary thermodilution (TPTD) as well as the risk for transfusion‐related acute lung injury (TRALI). We compared hemodynamic parameters obtained before and after a total of 30 sessions of TPE treatment in 10 intensive care unit patients. Among standard hemodynamic parameters, heart rate ( P  < 0.012) and systolic blood pressure ( P  < 0.008) significantly increase, whereas neither mean arterial pressure nor diastolic blood pressure was altered after TPE. The TPTD‐derived cardiac function parameters, cardiac index (CI; P  = 0.035), cardiac power index (CPI; P  = 0.008), global ejection fraction (GEF; P  = 0.002), and stroke volume index (SVI; P  = 0.014), were significantly higher after TPE. Furthermore, systemic vascular index significantly increased ( P  < 0.042). Among the cardiac preload parameters, central venous pressure was significantly lower after TPE ( P  < 0.001), while the global end‐diastolic volume index (GEDVI) did not change. Contractility marker dPmax did not change. Finally, TPE application did not significantly alter the pulmonary hydration and permeability parameters, extravascular lung water index (EVLWI) and pulmonary vascular permeability index. Vasopressor dose was not statistically significantly altered. Considering increases in SVI, CI, GEF, and CPI and stable values for GEDVI, EVLWI, and dPmax, our data do not give any hint for hemodynamic impairment or TRALI.